Budget Participation and Managerial Performance with Organizational Commitment and Leadership Style as A Moderation - Mulyanah Mulyanah; Intan Puspanita (Jurnal Riset Akuntansi Terpadu, 2021)
The purpose of this research to know the effect of budgetary participation on managerial performance, whether organizational commitment moderates the effect of budgetary participation on managerial performance and leadership style moderates the effect of budgetary participation on managerial performance. This research uses primary data. The population in this study are managers who work in manufacturing companies in the city of Cilegon, Banten Province. Samples were taken using the purposive sampling method. Data analysis uses linear regression and moderated regression analysis. The result of this study stated that budgetary participation had a positive effect on managerial performance, organizational commitment, and leadership style moderating with the effect of strengthening the effect of budgetary participation on managerial performance.